Evaluation of IgG4 subclass antibody detection by peptide-based ELISA for the diagnosis of human paragonimiasis heterotrema - Pewpan M. Intapan (2018)
A synthetic peptide was prepared based on the antigenic region of Paragonimus westermani pre-procathepsin L, and its applicability for immunodiagnosis for human paragonimiasis (due to Paragonimus heterotremus) was tested using an ELISA to detect IgG4 antibodies in the sera of patients. Sera from other helminthiases, tuberculosis, and healthy volunteers were used as the references. This peptide-based assay system gave sensitivity, specificity, accuracy, and positive and negative predictive values of 100%, 94.6%, 96.2%, 100%, and 88.9%, respectively. Cross reactivity was frequently seen against the sera of fascioliasis (75%) and hookworm infections (50%). Since differential diagnosis between paragonimiasis and fascioliasis can be easily done by clinical presentation and fascioliasis serology, this cross reaction is not a serious problem. Sera from patients with other parasitoses (0-25%) rarely responded to this synthetic antigen. This synthetic peptide antigen seems to be useful for development of a standardized diagnostic system for paragonimiasis. © 2013, Korean Society for Parasitology and Tropical Medicine.